Switch-matrix-based Monolithic CMOS Platform Featuring a Large Array of Carbon Nanotube Sensor Elements and a 96-channel Readout Circuitry. (2016) - Dudina, Alexandra; Seichepine, Florent; Chen, Yihui; Stettler, Alexander; Hierlemann, Andreas; Frey, Urs
Abstract: We present a monolithic CMOS biosensor system comprised of a switch-matrix-based array of carbon nanotube field-effect transistors (CNT-FETs) and an associated readout circuitry. The switch-matrix allows for flexible selection and simultaneous routing of 96 sensor elements to the readout channels. The resistances of the CNT-FETs were measured by applying a constant voltage and measuring the resulting current. Variation of the first-stage-amplifier gain and bandwidth allows for measuring resistances in the range between 50 kΩ and 20 MΩ at a bandwidth of up to 20 kHz. A parallel integration of the CNT-FETs has been achieved by using a floating electrode dielectrophoresis (DEP) manipulation technique.